Literatura fantástica de Charles Dickens em tradução: O sinaleiro e Quatro histórias de fantasmas no sistema literário brasileiro - Brunismann, Danielle Franco (2020)
This research aims to analyze the translation of the fantastic elements in Charles Dickens' tales. For this purpose two short stories were selected, the first entitled "The signalman", was published in 1866 in the journal All the Year Round, in the special Christmas volume. This tale has already received several translations into Brazilian Portuguese, for this research the translation "O sinaleiro", by Ricardo Lísias, published in 2004 in the book Contos Fantásticos do Século XIX chosen by Italo Calvino was selected. The tale "Four ghost stories", still unpublished into Brazilian Portuguese, had its translation done as one of the objectives of this research work. For the development of this research project, it was first necessary to build a mapping of the tales already inserted in the Brazilian literary system. The data collection was done by consulting physical editions of books, consulting the websites of publishers and second-hand bookstore, in addition to consulting the collection of the National Library of Brazil. Given this mapping, no translations into Brazilian Portuguese of the short story "Four ghost stories" were found, thus presenting this possibility. The theoretical contribution includes theorists of Descriptive Studies and the School of Manipulation or Cultural Turn, in Translation Studies, such as Gideon Toury (2012) and Itamar Even-Zohar (1990), Lawrence Venuti (2002), Antoine Berman (2007) and Rafael Lanzetti et. al. This research investigated the construction of the chain of signifiers and the choices of lexical terms applied to translations, in order to identify how to translate the fantastic elements and to create both the natural and supernatural atmosphere. For the analysis of the Fantastic aspects, the studies of Howard Phillip Lovecraft (1987), Remo Ceserani (2006), Tzvetan Todorov (2003) and (2006), David Roas (2014) were used as a basis. Fred Botting (1996), Maurício Menon (2007), (2011) and (2013) and Edgar Allan Poe (1999) were used for the conceptualization of Gothic and the elements of narrative composition. At the end of the analysis, it was found that in "The signalman the chains of signifiers related to the thematic axes of space, fear and the supernatural, were analyzed and it was considered that they were maintained when translated into Brazilian Portuguese, however, there was in some lexical items a softening of the intensity of the adjectives used. In the analysis of the translation of "Four ghost stories" it is observed that the objectives established in the translation project were achieved, as well as difficulties that exist in the translation activity. Regarding the translation of the elements of the fantastic, it was observed that the meanings created by the author were maintained in the target text.